Eksistensialisme dalam Cerpen Laki-Laki Pemanggul Goni Karya Budi Darma - Engkin Suwandana (ELite Journal : International Journal of Education, Language, and Literature, 2019)
Laki-laki Pemanggul Goni" by Budi Darma is one example of existentialism in literature. This literature work shows freedom, love, guilt, failure, alienation and death. The aim of this descriptive qualitative study was describing the concept of existentialism in this short story based on the six main topics of the story. Freedom topic was reflected in; there are five hunters, including him, Karmain's father. The five of them entered the woods together, and then saw a wild boar running fast, bumped into some bushes. In order to chase the boar, they splited up into different directions. One of his four friends accidentally shot Karmain's father, or intentionally shot him, nobody knows. Love topic is reflected in; when Karmain arrived back at his apartment, the raggedy man was already inside, sitting on a prayer mat, chanting the holy verses, while his gunny was next to him. Guilt was reflected in; Karmain stared at her mother's photo for a long time, then unconsciously, he sobbed. Her mother had once told him that at certain times there would be a raggedy man, visiting the sinners. The duty of the raggedy man was taking lives then put his victim's life into the gunny. Failure was reflected on; when the Karmain was on the road, the raggedy man didnot exist. The wind was still blowing hard. A black dog, big and tall, watched for a moment, and then crossed the street, and halfway down the road stopped, watched the other again, then ran toward the darkness. Then came dog howls, howls of pain, and howls of death. Alienation wass reflected in; In the lonely time, the raggedy man must be standing in the middle of the road, and when the streets are crowded, the burlap shoulder stands on the sidewalk, not far from the bushes, which when it is quiet and the wind is loud, it always makes the sounds which is very heart-wrenching. Death wass reflected in; almost a quarter of the houses in the village buried in flames, and two paralyzed men died, trapped by flames. Keywords: Existentialism, literature work